Compatibility of Kraft Lignin, Organosolv Lignin and Lignosulfonate With PLA in 3D Printing. (2nd January 2019) - Mimini, Vebi; Sykacek, Eva; Syed Hashim, Sharifah Nurul Ain; Holzweber, Julian; Hettegger, Hubert; Fackler, Karin; Potthast, Antje; Mundigler, Norbert; Rosenau, Thomas
Abstract : The compatibility of three different types of lignin, such as Kraft lignin, Organosolv lignin, and lignosulfonate, with PLA, in particular without the addition of any further reagents or compatibilizers, is investigated. The unmodified lignins were thoroughly characterized to establish their interaction potential in lignin-PLA composite formation. The obtained double-extruded binary systems containing 5, 10, and 15 wt % lignin in PLA were characterized in terms of chemical conversion ( 31  P NMR), thermal behavior (TGA, DSC), and cellular morphology (SEM). Additionally, the flexural and impact properties as well as the melt volume rate (MVR) of the extruded materials, in the form of 3D-printed bars, were analyzed, and the effect of lignin addition to PLA studied. The results revealed poor mechanical properties for the Kraft lignin-PLA blends, but higher compatibility of Organosolv lignin-PLA blends. Lignosulfonate-PLA blends showed a promising behavior for 3D-printing. A special nucleation effect, potentially useful in foaming applications, was observed in this study.